An application of logistic regression for analyzing transit advertising characteristics / Sakinah Mat Zin and Nor Aini Hassanuddin - Mat Zin, Sakinah; Hassanuddin, Nor Aini (Universiti Teknologi MARA, Pulau Pinang, 2014)
Transit advertising is a medium of advertising that reaches people who use public transport. This study involved a survey commissioned to obtain LRT main-users’ response towards transit advertising. This paper investigates the factors influencing the effectiveness of transit advertising. With the awareness and perception as the independent variables, this paper examines how these factors influence the receptivity as well as the effectiveness of transit advertising. Proportionate Stratified Random Sampling is used to obtain the sample by location of the LRT stations. A personally-administered questionnaire was distributed randomly among respondents at nine selected LRT stations. Descriptive analysis was used to gauge the insidious factors that influence users’ awareness by using the Pearson Chi-Sq test. 33.9% of the respondents opted to purchase and use the advertised products or services in the near future. Only a small number of the respondents would immediately buy the advertised products. Nonetheless, awareness is only triggering a low impact on them in determining whether they will or will not purchase the advertised products. Logistic regression is used to find further relationship between awareness and perception with receptivity. From the analysis, it has been found that awareness towards the advertisement is the only factor that influences respondents’ desire towards the advertised products. Those who are aware of the advertisement were about 3.5 times more likely to buy or try the product compared to the respondents who were not aware of the advertisement placed in the vicinities. Findings of this study will provide an insight to the management in evaluating the effectiveness of transit advertising.